On the stellar halo metallicity profile of Milky Way-like galaxies in the Auriga simulations - Monachesi, Antonela; Grand, Robert J. J.; Springel, Volker; Pakmor, Rüdiger (Arxiv, 2016)
A recent observational study of haloes of nearby Milky Way-like galaxies shows that only half (four out of eight) of the current sample exhibits strong negative metallicity ([Fe/H]) gradients. This is at odds with predictions from hydrodynamical simulations where such gradients are ubiquitous. In this Letter, we use high resolution cosmological hydrodynamical simulations to study the [Fe/H] distribution of galactic haloes. We find that kinematically selected stellar haloes, including both in-situ and accreted particles, have an oblate [Fe/H] distribution. Spherical [Fe/H] radial profiles show strong negative gradients within 100 kpc, in agreement with previous numerical results. However, the projected median [Fe/H] profiles along the galactic disc minor axis, typically obtained in observations, are significantly flatter. The median [Fe/H] values at a given radius are larger for the spherical profiles than for the minor axis profiles by as much as 0.4 dex within the inner 50 kpc. Similar results are obtained if only the accreted stellar component is considered indicating that the differences between spherical and minor axis profiles are not purely driven by heated disc star particles formed in situ. Our study highlights the importance of performing careful comparisons between models and observations of halo [Fe/H] distributions.